Advances in Data and Information Sciences Proceedings of ICDIS-2017, Volume 1 - Kolhe, Mohan L.; Trivedi, Munesh C.; Tiwari, Shailesh; Singh, Vikash Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book gathers a collection of high-quality peer-reviewed research papers presented at the International Conference on Data and Information Systems (ICDIS 2017), held at Indira Gandhi National Tribal University, India from November 3 to 4, 2017. The book covers all aspects of computational sciences and information security. In chapters written by leading researchers, developers and practitioner from academia and industry, it highlights the latest developments and technical solutions, helping readers from the computer industry capitalize on key advances in next-generation computer and communication technology.
Computation of Dynamic Signal Phases for Vehicular Traffic -- Disctrete Wavelet Transform and kNN Based Fault Detector and Classifier for PV Integrated Microgrid -- Automated Tool for Extraction of Software Fault Data -- Comparative Study of Mobile Forensic Tools -- Implementing Image Compression and Cryptography on Fractal Images -- Computer Aided Diagnosis of Melanoma Skin Cancer: A Review -- Computer Vision Based Tomato Grading and Sorting -- Movie Recommendation System Using Genome Tags and Content-based Filtering -- Leveraging Machine Learning in Mist Computing Telemonitoring System for Diabetes Prediction -- A Novel Energy Ecient Hybrid Full Adder Circuit -- An Insight into Theory-Guided Climate Data Science - A Literature Review -- Fusion of Signal and Differential Signal Domain Features for Epilepsy Identification in Electroencephalogram Signals.
Keywords: Telecommunication; Data mining; Computational intelligence; Communications Engineering, Networks; Data Mining and Knowledge Discovery; Computational Intelligence